1999
DOI: 10.1023/a:1007034508547
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study investigates the morphological and molecular changes that occur in the inner hair cell area of the rat cochlea following aminoglycoside treatment. Rats were injected daily with 500 mg/kg of amikacin between postnatal day 9 (PND9) and PND16. Cochleae were examined at PND16 to PND120 using both scanning and transmission electron microscopy and molecular fluorescent labeling. The inner hair cells showed obvious signs of apoptosis in response to amikacin treatment and most of them were missing by one we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…3, d, e). These changes can be seen after treatment with aminoglycosides, cisplatin, under conditions of chronic renal insufficiency, and chronic noise exposure [2][3][4][5]8,9,11,13]. This process is asynchronous in neighboring cells, which fact explains the presence of just solitary apoptosis figures in tissues (in contrast to necrosis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, d, e). These changes can be seen after treatment with aminoglycosides, cisplatin, under conditions of chronic renal insufficiency, and chronic noise exposure [2][3][4][5]8,9,11,13]. This process is asynchronous in neighboring cells, which fact explains the presence of just solitary apoptosis figures in tissues (in contrast to necrosis).…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic death of some HC is followed by compensatory hypertrophy of Deiters' supporting cells (Fig. 3, e) with the formation of a permanent "epithelial cicatrix" [11], due to which the intact surface of the reticular plate is retained and further structural and functional disorders of acoustic perception at the adjacent OC sites with intact HC are prevented. b a c e d Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While many cell types in the inner ear internalize aminoglycosides, the HCs are particularly vulnerable to aminoglycoside-induced death. Aminoglycoside-induced HC death has been described as both apoptotic and necrotic (Nakagawa et al, 1998 ; Lenoir et al, 1999 ; Matsui et al, 2002 , 2003 ; Cunningham et al, 2004 ; Jiang et al, 2005 ). The molecular and cellular mechanisms that result in HC death are not fully understood, but there are a number of signaling molecules that are associated with aminoglycoside ototoxicity.…”
Section: Ototoxicitymentioning
confidence: 99%
“…In the inner ear, moderate doses of ototoxins such as aminoglycosides or cisplatin have been shown to induce auditory sensory cell apoptosis in vitro [7][8][9] and in vivo [10][11][12]. Several recent publications studying the biological effects of sound and impulse sound trauma revealed that apoptosis is the predominant mode of hair cell death following such sound trauma [13][14][15].…”
Section: Apoptosis (Type 1)mentioning
confidence: 99%